Development of sign language videos to improve mathematical communication of deaf students of fractional material - Utari Oktaviani; Fadhilah Rahmawati; Megita Dwi Pamungkas (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
As many as 7.03% of people with disabilities in Indonesia are deaf people. The problem for deaf students is the lack of mathematics learning resources during learning and the low mathematical communication skills of deaf students. The purpose of this study is to analyze the development of sign language learning videos to improve mathematical communication of deaf students of fractional material in terms of validity, practicality, and effectiveness. The method used is the R&D method with a 4D model. The results showed that the validity of the media resulted in a very valid category by sign language experts with a score of 85% and material experts with a score of 83% and categories valid by media experts with a score of 78.5%. The results of media practicality of 100% for teacher and student responses and learning implementation questionnaires are said to be very practical. The results of the control class pretest and the experiment resulted in a sig value. > 0.05, then the data is normal. Homogeneity test with (6,14) <  (19) on pretest questions and (4,68) <  (19) on posttest questions then homogeneous data. Student scores resulted in a difference in the average student learning outcomes between the experimental class and the control class indicated by the T test results with the sig value. (0.001) < 0.05. The average value of the N Gain of the experimental class is greater than that of the control class, which is 0.9721 with a high category. so that the media is said to be valid, practical, and effective.